Landscape of Inclusive Business Models of Healthcare in India : Business Model Innovations - International Finance Corporation (World Bank, New Delhi, 2017)
International Finance Corporation (IFC) defines inclusive business models (IBM) as enterprises that help expand access to goods, services, and livelihood opportunities to those at the base of the pyramid in commercially viable, scalable ways. The context of India - poor health indicators, a globalized economy, the government’s willingness to work with the private sector, and recognition of the poor as clients rather than beneficiaries - has led to the emergence of inclusive business models in the Indian economy. A number of for-profit and not-for-profit organizations have emerged as inclusive business models in India. Also, many organizations work with the government to provide healthcare services through public-private partnership (PPP) models. This IFC and Wadhwani Initiative for Sustainable Healthcare (WISH) study provides an overview of the landscape of inclusive business models in the healthcare sector. It includes challenges they face, strategies they adopt to succeed, and suggestions on how the ecosystem can enable and facilitate their growth.